Aspectos da representação temática pela indexação de livros: análise de Assunto e suas concepções na diversificação de áreas do conhecimento em bibliotecas dos Institutos Federais de Educação, Ciência e Tecnologia (IF's) - Sousa, Brisa Pozzi de [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The thematic representation of information, aimed at providing documentary information trough on-line catalogs of libraries, has required the area of Information Treatment and Organization the development of theoretical and instrumental subsidies to assist in analysis, synthesis and representation of the documentary contents, seeking contributions for both theoretical sedimentation of Information Science, and to promote the professional practice of librarians. The intention of researching the process of subject analysis in indexing arises from the need for empirical work in this field, once many difficulties surround the area, and perceives a small number of investigative. It is intended to contribute to the Information Treatment, both as a research phase of the sphere thematic, as for professional practice, showing how the data collected and the results can help proposals to be explored in future research. In this context, it is proposed an investigation into the thematic representation of books by catalogers during subject analysis in cataloging, from the content-oriented and requirements-oriented conceptions, in order to produce the documentary information, in catalogs of university libraries. By means of bibliographic exploratory investigation into field, with qualitative approach, this research aims to contribute to the indexer can refer more attention to the thematic representation of the document, expanding their outlook on the importance of the process of subject analysis. The results indicate that for the preparation of thematic representation in the subject analysis for indexing, which result in the documentary information in the catalogs, it is important to note the explicit and implicit information in the document... (Complete abstract click electronic access below)

A representação temática da informação, visando a disponibilização da informação documentária nos catálogos on-line das bibliotecas, tem exigido da área de Organização e Tratamento da Informação o desenvolvimento de aportes teóricos e instrumentais que auxiliem nos procedimentos de análise, síntese e representação do conteúdo documentário, buscando contribuições tanto para a sedimentação teórica da Ciência da Informação, quanto para fomentar a prática profissional de bibliotecários. A intenção de pesquisar o processo de análise de assunto na indexação surge da necessidade empírica de trabalho nesse campo, pois muitas dificuldades circundam a área e percebe-se o pequeno número de investigações. Pretende-se contribuir com o Tratamento da Informação, tanto como etapa de pesquisa da esfera temática, quanto para o fazer profissional, demostrando como os dados coletados e os resultados obtidos podem auxiliar propostas a serem exploradas em futuras pesquisas. Neste contexto, propõe-se uma investigação sobre a representação temática de livros por catalogadores, durante a análise de assunto na catalogação, a partir das concepções orientadas para o conteúdo e pela demanda para produzir a informação documentária, em catálogos de bibliotecas universitárias. Por meio da investigação exploratória bibliográfica de campo, com abordagem qualitativa, esta pesquisa visa contribuir para que o indexador possa remeter mais atenção à representação temática do documento, alargando sua visão sobre a importância do processo de análise de assunto. Os resultados obtidos sinalizam que para a elaboração da representação temática na análise de assunto pela indexação, que originará a informação...
Keywords: Indexação; Catalogação - Processamento de dados; Ciência da informação